Nietzsche's dancers : Isadora Duncan, Martha Graham, and the revaluation of Christian values - LaMothe, Kimerer L. (Palgrave Macmillan, 2006)
Nietzsche uses images of dance throughout his work to represent the process and the fruits of his "revaluation of all values." American modern dancers Isadora Duncan and Martha Graham were inspired by his work as they created their respective visions for what dance can and should be. This book examines the relationships among these three figures, arguing that the techniques of dance practice, choreography, and performances developed by Duncan and Graham critically advance Nietzsche's revaluation of Christian values.